Research on the Modular Design Strategy of Old Community Facilities for the Elderly based on "Gerontology" - Zhou, Zifan; Zong, Cheng; Chen, Xiaohua; Wu, Qiuxiao; Bai , Yuwei (Transactions on Social Science, Education and Humanities Research, 2024)
With the intensification of the aging of the population, the adaptation of community space to the elderly has become an important issue that needs urgent attention in the renewal of community space. In view of the contradiction between the current public space facilities in old communities that are difficult to meet the growing needs of the elderly, this paper takes the old communities in Beijing as the research object, studies the modular design of the facilities suitable for the elderly in the old communities based on the behavioral needs of the elderly, analyzes the existing space problems and the needs of the elderly through site research and questionnaires, and finally puts forward design strategies and design schemes to provide ideas for the renewal of old community spaces.